The Role of Neutrophil Lymphocyte Ratio as a Major Adverse Cardiac Events Predictor and Its Correlation with Coronary Severity in Acute Coronary Syndrome Patients with Chronic Kidney Disease: A Case Control and Cross-Sectional Study - Immanuel, Suzanna; Ginanjar, Eka; Imanina Putri Nurtyas, Fahrani; Sukartini, Ninik; Yusra, Yusra; Pasaribu, Merci Monica B. R. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Acute coronary syndrome (ACS) patients with chronic kidney disease (CKD) are known to have a higher risk of mortality compared to ACS patients without CKD. In ACS patients with CKD, chronic inflammation plays an important role in morphological and functional changes in endothelial cells, resulting in atherosclerosis acceleration associated with coronary severity that leads to an increase in major adverse cardiac events (MACE). AIM: Therefore, this study aims to determine the role of neutrophil lymphocyte ratio (NLR) as a predictor of MACE and its correlation with coronary severity in ACS patients with CKD. METHODS: The study was conducted at National General Hospital Cipto Mangunkusumo Jakarta, Indonesia in October to November 2019. We used quota sampling with two designs study. First, a nested case control study was conducted with a total of 59 ACS patients with CKD: 31 subjects who had experienced MACE as a case group and 28 subjects who had not experienced MACE as a control group. Second, a correlative study with a cross-sectional approach was undertaken. RESULTS: There was no significant difference or relationship between NLR and MACE (p > 0.05; OR = 2.16 [95% CI = 0.63–7.51]), also no correlation between NLR and coronary severity degree assessed using the Gensini score (r = 0.10; p = 0.474). CONCLUSION: NLR can not predict MACE in ACS patients with CKD nor be employed interchangeably with the Gensini score in assessing coronary severity in ACS patients with CKD.